Implantação e avaliação de infraestrutura avançada de medição de energia em uma instituição pública - Vizzotto, William Dotto (2020)
The electricity distribution system is becoming more complex, when compared to the transmission and generation ones. However, the arrival of new technologies, such as distributed generation and smart electricity grids, demands a change of vision regarding the simplicity of energy distribution. One of the technologies that has been studied and implemented throughout the world is the Advanced Metering Infrastructure. This work was dedicated to study and implement a system of the type, evaluating all the challenges and benefits that such technology can bring to a public institution. System requirements were defined, and based on that, the technologies used were defined. The proposed system consists of 60 smart energy meters installed in different buildings at the Federal University of Santa Maria, a long-range communication network that operates in an unlicensed band and a data management system based on open source technologies. The application makes it possible to carry out electrical energy quality analysis and individualization of the loads that make up the UFSM campus, providing a range of information to the maintenance teams and for guiding energy efficiency actions. The results obtained indicate some drawbacks in relation to the communication network, however, the feasibility of implementing the system was verified, with a survey of energy quality indicators and individualization of energy consumption and demand for various buildings during the month of December 2019. Finally, there was a list of suggestions for future work that may contribute to improve the performance of the implemented AMI.